African Trypanosomiasis in Young Female in North India - A Rare Case Report - Parwan, Deepika; kumar, Ranjan; Aggrawal, Sumit (Annals of Pathology and Laboratory Medicine, 2021)
Human African trypanosomiasis, also known as sleeping sickness, is a vector-borne parasitic disease. It is caused by infection with protozoan parasites belonging to the genus Trypanosoma. They are transmitted to humans by tsetse fly (Glossina genus) bites which have acquired their infection from human beings or from animals harboring human pathogenic parasites. Tsetse flies are found just in sub-Saharan Africa though only certain species transmit the disease. We report a case of human African trypanosomiasis in a 28-year-old Indian female who had a travel history to sub–Saharan Africa, Uganda and she presented with a history of fever, body ache, headache, decreased oral intake, pain lower abdomen, swelling and discharge from forearm chancre since last 4-5 days. Peripheral smear showed heavy parasitemia by flagellated forms of Trypanosoma and the diagnosis of Trypanosoma brucei was given on Peripheral smear report. Serological testing was also done and a diagnosis of West-African trypanosomiasis was confirmed. The patient was successfully treated and made a good recovery. So West-African trypanosomiasis should be considered in the differential diagnosis with presentation of fever with chancre in every person with recent history of travel to African countries as it is universally fatal without treatment.